Sistem Penggajian Berbasis Rekap Data Absensi Pegawai pada Dinas Lingkungan Hidup, Kehutanan, dan Pertanahan Provinsi Papua Tengah - Yosep Stenly Pigai; Cici Kamalia (STMIK Pesat Nabire, 2026)
Digital transformation in the management of personnel administration at the Environment, Forestry, and Land Service of Central Papua Province has brought significant changes in the employee payroll and attendance system. This study aims to design and implement an integrated attendance data recap-based payroll information system. The research method used is the Waterfall approach, which includes needs analysis, system design, and implementation. The results of the study indicate that the developed system is able to increase efficiency and accuracy in managing attendance data and calculating salaries, as well as minimizing human error. In addition, the application of web-based technology with geolocation features allows real-time attendance monitoring, which is very important for employees working in the field. However, challenges in technology adoption, such as limited infrastructure and low technological literacy among employees, still need to be overcome. This study is expected to contribute to creating a more professional, transparent, and accountable human resource governance.